High-performance integrated gel ion diode and preparation method and application thereof
Through digital photocuring 3D printing technology, P-type, diaphragm and N-type hydrogels are printed to form an integrated gel ion diode, which solves the problems of insufficient conductivity and rectification performance of existing gel ion diodes and achieves high performance and simplification Preparation effect.
Patent Information
- Application Number
- CN202411460479.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-02-11
AI Technical Summary
The existing gel ion diodes have shortcomings in conductivity and rectification performance, and are complex in assembly, making them difficult to effectively apply in circuits.
Using digital photocuring 3D printing technology, cured P-type semiconductor hydrogel, membrane hydrogel and N-type semiconductor hydrogel are successively printed to form an integrated high-performance gel ion diode. This method uses polyacrylamide as a hydrogel matrix and adds MXene and polymer electrolyte to improve conductivity and rectification characteristics.
Gel ion diodes with high conductivity and high rectification characteristics are achieved, which simplifies the preparation process and is suitable for practical circuits and replaces the functions of traditional diodes.
Smart Images

Figure CN119421592A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of gel electronics, and specifically refers to a high-performance integrated gel ion diode and a preparation method and application thereof. Background Art
[0002] The development of plasma electronic devices such as new energy batteries and supercapacitors has greatly promoted the transformation and upgrading of energy and the progress of the Internet of Things, making ion electronics more widely concerned. Compared with traditional electronic electronics, current ion electronics does not have the ability to assemble complete circuits. The reason is the lack of basic ion electronic components with excellent performance and easy assembly, such as ion diodes.
[0003] Ionic diodes are mainly divided into four types: thin film type, asymmetric composition type, gel type and elastomer type. Thin film type and asymmetric composition type are difficult to apply to circuits due to their complex preparation, hard texture, mismatched rectification mechanism and other disadvantages. The elastomer type does not contain solvents inside, resulting in slow ion transmission rate and poor conductivity, and has high energy consumption when used in circuits. Gel-based ionic diodes have great application potential in actual circuits due to their flexibility, biocompatibility, fast ion transmission rate and other advantages.
[0004] In practical applications, gel ion diodes also face some problems. The first is conductivity. Although the three-dimensional network structure and liquid medium of the gel are conducive to the transmission of ions, its conductivity still cannot meet the needs of practical applications. It is necessary to add conductive fillers to the P-type and N-type semiconductor gels to improve the conductivity. Secondly, after adding conductive fillers, the direct contact between the P-type and N-type gels may cause a short circuit. Usually, the short circuit can be avoided by adding a diaphragm, but due to the difference in ion transmission behavior between the gel and the diaphragm, it may have a certain impact on the rectification performance of the gel ion diode. Finally, the addition of the diaphragm increases the assembly process of the gel ion diode and the circuit, and the realization of the circuit function is easily affected by the assembly of the gel ion diode. Summary of the invention
[0005] The purpose of the present invention is to provide a gel ion diode with good conductivity and rectification, and at the same time provide a simple and easy-to-implement preparation method thereof, as well as the application of the gel ion diode.
[0006] To achieve the above objectives, the present invention provides a high-performance integrated gel ion diode, which includes, from top to bottom, a P-type semiconductor hydrogel, a diaphragm hydrogel and an N-type semiconductor hydrogel, and the P-type semiconductor hydrogel, the diaphragm hydrogel and the N-type semiconductor hydrogel are integrally formed.
[0007] As a further solution of the present invention: the hydrogel matrix in the P-type semiconductor hydrogel, the diaphragm hydrogel and the N-type semiconductor hydrogel is polyacrylamide.
[0008] A method for preparing a high-performance integrated gel ion diode utilizes digital light-curing 3D printing technology to sequentially print and cure a P-type semiconductor hydrogel solution, a diaphragm hydrogel solution, and an N-type semiconductor hydrogel solution, so that these solutions are cured into gels to form a P-type semiconductor hydrogel, a diaphragm hydrogel, and an N-type semiconductor hydrogel.
[0009] As a further solution of the present invention: the digital light-curing 3D printing technology comprises the following steps:
[0010] S1: Configuration of digital light-curing 3D printing ink:
[0011] P-type semiconductor hydrogel solution: Add acrylamide monomer, phenyl-2,4,6-trimethylbenzoylphosphonate lithium salt powder, and N,N'-methylenebisacrylamide powder to water, stir for 20 minutes, so that the solid is completely dissolved and the solution becomes clear and transparent; add MXene powder to the above solution, ultrasonicate for 1 hour, and finally add polymer electrolyte sodium poly(p-styrene sulfonate), continue stirring for 20 minutes, mix the two evenly, and stir until the powder is completely dissolved; the mass fraction of the acrylamide monomer is 10%-20%, the mass fractions of phenyl-2,4,6-trimethylbenzoylphosphonate lithium salt and N,N'-methylenebisacrylamide are 0.05%-0.1% and 0.05%-0.08% respectively, the mass fraction of sodium poly(p-styrene sulfonate) is 5%-10%, and the concentration of MXene is 0-1mg / ml. The MXene powder is an accordion-like multilayer MXene nanosheet;
[0012] Diaphragm hydrogel solution: acrylamide monomer, phenyl-2,4,6-trimethylbenzoylphosphonate lithium salt powder, N,N'-methylenebisacrylamide powder and lemon yellow powder are added into water and stirred for 20 minutes to completely dissolve the solid and make the solution clear and transparent; wherein the mass fraction of acrylamide monomer is 10%-20%, the mass fractions of phenyl-2,4,6-trimethylbenzoylphosphonate lithium salt powder, N,N'-methylenebisacrylamide powder and lemon yellow are 0.05%-0.1%, 0.05%-0.08% and 0.01%-0.02% respectively;
[0013] N-type semiconductor hydrogel solution: acrylamide monomer, phenyl-2,4,6-trimethylbenzoylphosphonate lithium salt powder, and N,N'-methylenebisacrylamide powder are added to water and stirred for 20 minutes to completely dissolve the solid and make the solution clear and transparent; then polydiallyldimethylammonium chloride solution is added to the above solution; stirring is continued for 20 minutes, and finally MXene powder is added and ultrasonicated for 1 hour; wherein the mass fraction of acrylamide monomer is 10%-20%, the mass fractions of phenyl-2,4,6-trimethylbenzoylphosphonate lithium salt and N,N'-methylenebisacrylamide are 0.05%-0.1% and 0.05%-0.08% respectively, the mass fraction of polydiallyldimethylammonium chloride is 3%-5%, and the concentration of MXene is 0-1mg / ml;
[0014] S2: Digital light-curing 3D printing:
[0015] After slicing according to the designed model, the P-type semiconductor hydrogel solution is printed and solidified first, and then the diaphragm hydrogel solution and the N-type semiconductor hydrogel solution are printed and solidified in sequence, wherein the acrylamide monomers in each solution form polyacrylamide gel solids under digital light irradiation; finally, the high-performance integrated gel ion diode is formed by integrated molding.
[0016] As a further solution of the present invention: the model is cylindrical, the radius of the model is 5-10 mm, the total thickness is 2.5-3 mm, the layer height of the 3D printing is set to 100 μm, and the curing time is 10-15 s.
[0017] As a further solution of the present invention: the size of the integrated gel ion diode is a radius of 5-10 mm and a total thickness of 2.5-3 mm; wherein the thickness of the diaphragm hydrogel is 0.5-1 mm.
[0018] The invention discloses an application of a high performance integrated gel ion diode in a circuit.
[0019] Compared with the prior art, the present invention uses digital light-curing 3D printing technology to sequentially print and cure P-type semiconductor hydrogel solution, diaphragm hydrogel solution and N-type semiconductor hydrogel solution, and integrates them to obtain a high-performance integrated gel ion diode, which is simple to prepare. The hydrogel matrix is polyacrylamide, and the rectification characteristics are achieved by sodium polystyrene sulfonate in the P-type solution and polydiallyl dimethyl ammonium chloride in the N-type solution. The integrated molding process and the addition of MXene improve the conductivity and rectification characteristics. Due to the high conductivity and high rectification characteristics, the integrated gel ion diode can be used in actual circuits. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a structural schematic diagram of the high-performance integrated gel ion diode of the present invention.
[0021] Figure 2 These are IV test graphs of integrated gel ion diodes of different thicknesses of the present invention; wherein FIG. a is the IV curve of the gel ion diode prepared in Example 1 at ±4V; FIG. b is the IV curve of the gel ion diode prepared in Example 2 at ±4V; FIG. c is the IV curve of the gel ion diode prepared in Example 3 at ±4V; and FIG. d is a comparison of the IV curves of the gel ion diodes in Example 1, Example 2 and Example 3.
[0022] Figure 3 It is an IV curve diagram of the effect of MXene on the performance of the gel ion diode in the present invention; wherein Figure a is the IV curve of the gel ion diode prepared in Example 1; Figure b is the IV curve of the gel ion diode prepared in Example 2; Figure c is the IV curve of the gel ion diode prepared in Example 2; Figure d is the IV curve performance of the gel ion diode in Example 1, Comparative Example 2 and Example 2.
[0023] Figure 4 Figure 2 is the IV curve and rectification ratio of gel ion diodes of different thicknesses at ±3V in the present invention; Figure a is the IV curve of the gel ion diodes in comparative example 1, comparative example 2 and embodiment 2 at ±3V; Figure b is the IV curve of the gel ion diodes in comparative example 3, comparative example 4 and embodiment 3 at ±3V; Figure c is the rectification ratio of the gel ion diodes in comparative example 1, comparative example 2 and embodiment 2 at ±3V; Figure d is the rectification ratio of the gel ion diodes in comparative example 3, comparative example 4 and embodiment 3 at ±3V.
[0024] Figure 5 It is a comparison of the rectification ratios of gel ion diodes of different thicknesses at ±4V in the present invention and the influence of MXene on the rectification ratio; wherein Figure a is the rectification ratio of the gel ion diodes at ±4V in comparative example five, comparative example six and embodiment one and the influence of MXene on the rectification capacity; Figure b is the rectification ratio of the gel ion diodes at ±4V in comparative example one, comparative example two and embodiment two and the influence of MXene on the rectification capacity; Figure c is the rectification ratio of the gel ion diodes at ±4V in comparative example three, comparative example four and embodiment three and the influence of MXene on the rectification capacity; Figure d is the rectification capacity of the gel ion diodes in embodiments one to three and ratios one to seven.
[0025] Figure 6 It is a circuit diagram of an integrated gel ion diode applied to a circuit; Figure a is a circuit schematic diagram of applying a reverse voltage, and Figure b is a circuit schematic diagram of applying a forward voltage.
[0026] In the figure: 1. P-type semiconductor hydrogel, 2. diaphragm hydrogel, 3. N-type semiconductor hydrogel. DETAILED DESCRIPTION
[0027] The present invention will be further described below in conjunction with the accompanying drawings.
[0028] like Figure 1 As shown, a high-performance integrated gel ion diode includes a P-type semiconductor hydrogel 1, a membrane hydrogel 2 and an N-type semiconductor hydrogel 3 from top to bottom, and the P-type semiconductor hydrogel 1, the membrane hydrogel 2 and the N-type semiconductor hydrogel 3 are integrally formed.
[0029] The hydrogel matrix in the P-type semiconductor hydrogel 1, the membrane hydrogel 2 and the N-type semiconductor hydrogel 3 is polyacrylamide.
[0030] The preparation method includes: using digital light-curing 3D printing technology to sequentially print and cure a P-type semiconductor hydrogel solution, a diaphragm hydrogel solution, and an N-type semiconductor hydrogel solution, so that these solutions are cured into gels to form a P-type semiconductor hydrogel 1, a diaphragm hydrogel 2, and an N-type semiconductor hydrogel 3.
[0031] Digital light-curing 3D printing technology includes the following steps:
[0032] S1: Configuration of digital light-curing 3D printing ink:
[0033] P-type semiconductor hydrogel solution: acrylamide (AAm) monomer, phenyl-2,4,6-trimethylbenzoylphosphonate lithium salt (LAP) powder, N,N'-methylenebisacrylamide (MBAA) powder are added to water and stirred for 20 minutes to completely dissolve the solid and make the solution clear and transparent; MXene powder is added to the above solution, ultrasonicated for 1 hour, and finally the polymer electrolyte poly(p-styrene sulfonate) sodium (PSSNa) is added and stirred for 20 minutes to mix the two evenly until the powder is completely dissolved; the mass fraction of the AAm monomer is 10%-20%, the mass fractions of LAP and MBAA are 0.05%-0.1% and 0.05%-0.08% respectively, the mass fraction of PSSNa is 5%-10%, and the concentration of MXene is 0-1mg / ml. The MXene powder is an accordion-like multilayer MXene nanosheet.
[0034] Diaphragm hydrogel solution: AAm monomer, LAP powder, MBAA powder and lemon yellow powder are added to water and stirred for 20 minutes to completely dissolve the solids and make the solution clear and transparent; wherein the mass fraction of AAm monomer is 10%-20%, and the mass fractions of LAP powder, MBAA powder and lemon yellow are 0.05%-0.1%, 0.05%-0.08% and 0.01%-0.02%, respectively.
[0035] N-type semiconductor hydrogel solution: AAm monomer, LAP powder, and MBAA powder are added to water and stirred for 20 minutes to completely dissolve the solid and make the solution clear and transparent; then polydiallyldimethylammonium chloride (PDACl) solution is added to the above solution; stirring is continued for 20 minutes, and finally MXene powder is added and ultrasonicated for 1 hour; wherein the mass fraction of AAm monomer is 10%-20%, the mass fractions of LAP and MBAA are 0.05%-0.1% and 0.05%-0.08% respectively, the mass fraction of PDACl is 3%-5%, and the concentration of MXene is 0-1mg / ml. The PDACl is a commercial product, and the mass fraction of PDACl in the final N-type semiconductor hydrogel solution is 3%-5%.
[0036] S2: Digital light-curing 3D printing:
[0037] After slicing according to the design model, the P-type semiconductor hydrogel solution is first printed and solidified, followed by the diaphragm hydrogel solution and the N-type semiconductor hydrogel solution, where the AAm monomers in each solution form polyacrylamide (PAAm) gel solids under digital light irradiation. Finally, the high-performance integrated gel ion diode is formed by integrated molding.
[0038] The model is cylindrical, the radius of the model is 5-10 mm, the total thickness is 2.5-3 mm, the layer height of the 3D printing is set to 100 μm, and the curing time is 10-15 s.
[0039] Then, the P-type semiconductor hydrogel, the diaphragm hydrogel and the N-type semiconductor hydrogel are tightly fitted together to form a cylindrical unified whole, that is, a high-performance integrated gel ion diode is formed; the size of the gel ion diode is a radius of 5-10mm and a total thickness of 2.5-3mm; the thickness of the P-type semiconductor hydrogel, the diaphragm hydrogel and the N-type semiconductor hydrogel is 0.5-1mm.
[0040] The rectification function of the diode of the present invention is evaluated by the rectification ratio, which is an indicator for evaluating the performance of ionic diodes and is defined as: the ratio of the current value corresponding to the forward voltage endpoint to the current value corresponding to the reverse voltage endpoint within the tested voltage range. The larger this value is, the better the rectification performance is. While achieving integrated molding, ensuring a high rectification ratio increases the difficulty of preparation to a certain extent.
[0041] In the gel ion diode of the present invention, the same material polyacrylamide is used as the matrix of the P-type semiconductor hydrogel, the diaphragm hydrogel and the N-type semiconductor hydrogel, which, on the one hand, ensures an integrated printing and molding process, and on the other hand, reduces the influence of multiple matrix materials on the performance.
[0042] Poly(sodium p-styrene sulfonate) (PSSNa) and poly(diallyl dimethyl ammonium chloride) (PDACl) are used as polymer electrolytes. The two polymer electrolytes dissociate in aqueous solution to form polymer molecular chains with certain charges (PSS - and PDA + ) and ions with opposite charges (i.e., counterions, Na + and Cl - ), the polymer molecular chains are fixed due to their certain viscoelasticity and the entanglement of the chains, while the counterions can move freely in the gel. After the integrated printing, due to the concentration difference, Na + and Cl - Migrate through the membrane hydrogel, from P-type to N-type and from N-type to P-type, respectively. At the junction, the polymer molecular chain forms a built-in electric field, which points from N-type to P-type. When a forward voltage is applied, the counterions move toward each other under the action of the electric field, reducing the energy barrier of the built-in electric field. At this time, the ion diode is in a conducting state; when a reverse voltage is applied, the counterions move in the opposite direction and gather near the electrode, increasing the energy barrier of the built-in electric field. At this time, the ion diode is in a cut-off state, realizing the forward conduction and reverse cut-off rectification characteristics similar to traditional diodes.
[0043] MXene is added as a conductive filler to P-type hydrogel and N-type hydrogel to improve conductivity, increase ion transfer rate, and significantly increase the current under forward voltage. Under reverse voltage, water molecules near the electrode undergo redox reactions to generate H + and OH - These two ions will also form a certain current under the action of reverse voltage, but due to the effect of the built-in electric field, the reverse current is much smaller than the forward current.
[0044] The application of the above-mentioned high-performance integrated gel ion diode can replace the traditional diode in some simple circuits to ensure the normal operation of the circuit.
[0045] Embodiment 1
[0046] A method for preparing a high-performance integrated gel ion diode comprises the following steps:
[0047] S1: Configuration of digital light-curing 3D printing ink:
[0048] P-type semiconductor hydrogel solution: add 0.4g acrylamide monomer, 2mg N,N'-methylenebisacrylamide, and 2.5mg phenyl-2,4,6-trimethylbenzoylphosphonate lithium salt to 2ml water, stir for 20 minutes to completely dissolve the solid, add 2mg MXene powder to the above solution, ultrasonicate for 1h, and finally add 0.15g sodium poly(p-styrene sulfonate) and stir until the solid is completely dissolved.
[0049] Diaphragm hydrogel solution: 0.8 g acrylamide monomer, 4 mg N,N'-methylenebisacrylamide, 5 mg phenyl-2,4,6-trimethylbenzoylphosphonate lithium salt, and 1 mg tartrazine were added to 4.2 ml water and stirred for 20 minutes to completely dissolve the solid.
[0050] N-type semiconductor hydrogel solution: Add 1.12g acrylamide monomer, 5mg N,N'-methylenebisacrylamide, and 6mg phenyl-2,4,6-trimethylbenzoylphosphonate lithium salt to 3.9ml water and stir for 20 minutes to completely dissolve the solid. Add 1.5g polydiallyldimethylammonium chloride (PDACI) solution to the above solution and continue stirring for 20 minutes. Finally, add 5.5mg MXene powder and ultrasonicate for 1h.
[0051] S2: Digital light-curing 3D printing:
[0052] According to the designed model, the printing layer height is set to 100μm. After the slicing is completed, 10 layers of P-type semiconductor hydrogel are first printed and cured, followed by 10 layers of membrane hydrogel, and finally 10 layers of N-type semiconductor hydrogel. The P-type semiconductor hydrogel, membrane hydrogel and N-type semiconductor hydrogel are closely fitted, and finally integrated into a high-performance integrated gel ion diode.
[0053] The radius of the prepared integrated gel ion diode is 7 mm and the total thickness is 3 mm, of which the thickness of the membrane hydrogel is 1 mm.
[0054] Embodiment 2
[0055] A method for preparing a high-performance integrated gel ion diode comprises the following steps:
[0056] S1: Digital light-curing 3D printing ink configuration:
[0057] P-type semiconductor hydrogel solution: add 0.4g acrylamide monomer, 2mg N,N'-methylenebisacrylamide, and 2.5mg phenyl-2,4,6-trimethylbenzoylphosphonate lithium salt to 2ml water, stir for 20 minutes to completely dissolve the solid, add 2mg MXene powder to the above solution, ultrasonicate for 1h, and finally add 0.15g sodium poly(p-styrene sulfonate) and stir until the solid is completely dissolved.
[0058] N-type semiconductor hydrogel solution: Add 1.12g acrylamide monomer, 5mg N,N'-methylenebisacrylamide, and 6mg phenyl-2,4,6-trimethylbenzoylphosphonate lithium salt to 3.9ml water and stir for 20 minutes to completely dissolve the solid. Add 1.5g polydiallyldimethylammonium chloride solution to the above solution and continue stirring for 20 minutes. Finally, add 5.5mg MXene powder and ultrasonicate for 1h.
[0059] Diaphragm hydrogel solution: 0.8 g acrylamide monomer, 4 mg N,N'-methylenebisacrylamide, 5 mg phenyl-2,4,6-trimethylbenzoylphosphonate lithium salt, and 1 mg tartrazine were added to 4.2 ml water and stirred for 20 minutes to completely dissolve the solid.
[0060] S2: Digital light-curing 3D printing:
[0061] According to the designed model, the printing layer height is set to 100μm. After the slicing is completed, 10 layers of P-type semiconductor hydrogel are first printed and cured, followed by 8 layers of diaphragm hydrogel, and finally 10 layers of N-type semiconductor hydrogel are printed and cured. The P-type semiconductor hydrogel, diaphragm hydrogel and N-type semiconductor hydrogel are closely fitted, and finally integrated into a high-performance integrated gel ion diode.
[0062] The radius of the prepared integrated gel ion diode is 7 mm and the total thickness is 2.8 mm, of which the thickness of the diaphragm hydrogel is 0.8 mm.
[0063] Embodiment 3
[0064] A method for preparing a high-performance integrated gel ion diode comprises the following steps:
[0065] S1: Digital light-curing 3D printing ink configuration:
[0066] P-type semiconductor hydrogel solution: add 0.4g acrylamide monomer, 2mg N,N'-methylenebisacrylamide, and 2.5mg phenyl-2,4,6-trimethylbenzoylphosphonate lithium salt to 2ml water, stir for 20 minutes to completely dissolve the solid, add 2mg MXene powder to the above solution, ultrasonicate for 1h, and finally add 0.15g sodium poly(p-styrene sulfonate) and stir until the solid is completely dissolved.
[0067] Diaphragm hydrogel solution: 0.8 g acrylamide monomer, 4 mg N,N'-methylenebisacrylamide, 5 mg phenyl-2,4,6-trimethylbenzoylphosphonate lithium salt, and 1 mg tartrazine were added to 4.2 ml water and stirred for 20 minutes to completely dissolve the solid.
[0068] N-type semiconductor hydrogel solution: Add 1.12g acrylamide monomer, 5mg N,N'-methylenebisacrylamide, and 6mg phenyl-2,4,6-trimethylbenzoylphosphonate lithium salt to 3.9ml water and stir for 20 minutes to completely dissolve the solid. Add 1.5g polydiallyldimethylammonium chloride solution to the above solution and continue stirring for 20 minutes. Finally, add 5.5mg MXene powder and ultrasonicate for 1h.
[0069] S2: Digital light-curing 3D printing:
[0070] According to the designed model, the printing layer height is set to 100μm. After slicing is completed, 10 layers of P-type semiconductor hydrogel are printed and solidified first, and then 5 layers of diaphragm hydrogel are printed and solidified on this basis. Finally, 10 layers of N-type semiconductor hydrogel are printed and solidified on the basis of the two to form a unified whole.
[0071] The radius of the prepared integrated gel ion diode is 7 mm and the total thickness is 2.5 mm, of which the thickness of the membrane hydrogel is 0.5 mm.
[0072] In the preparation process, each layer of hydrogel is cured by ultraviolet light-induced free radical polymerization through a digital light-curing 3D printer. Figure 1 In the internal structure diagram on the right, during the integrated molding process, polymerization reaction can also occur between each layer of hydrogel and they are connected by covalent bonds. In addition, the amino group (-NH2) on the polyacrylamide molecular chain can form intermolecular hydrogen bonds, which enhances the interaction between the layers of hydrogel and ensures the integration of the gel device.
[0073] Due to the addition of MXene, the upper and lower layers of P-type and N-type semiconductor hydrogels appear black. In order to easily distinguish the layers of hydrogels and facilitate 3D printing, lemon yellow is added to the membrane hydrogel to appear yellow. Examples 1 to 3 correspond to integrated gel ion diodes with membrane hydrogel thicknesses of 1 mm, 0.8 mm, and 0.5 mm, respectively.
[0074] The rectification characteristic is a significant characteristic of the diode, and the rectification ratio is a key parameter for evaluating the rectification characteristic. Figure 2 a, b, and c correspond to the IV curves of gel ion diodes with a total thickness of 3 mm, 2.8 mm, and 2.5 mm, respectively. To better compare the effect of the membrane hydrogel thickness on the IV curve, Figure 2 dFor Figure 2The test results of a, b, and c are summarized. It can be seen from the figure that as the thickness of the membrane hydrogel decreases, the forward current of the ion diode continues to increase. This is due to the decrease in the total migration distance of the counter ions, while the reverse current changes little, indicating that the ionic double layer plays a better control role in the movement of ions under reverse voltage.
[0075] Embodiment 4
[0076] A method for preparing a high-performance integrated gel ion diode comprises the following steps:
[0077] S1: Configuration of digital light-curing 3D printing ink:
[0078] P-type semiconductor hydrogel solution: add 0.24g acrylamide monomer, 1.18mg N,N'-methylenebisacrylamide, and 1.18mg phenyl-2,4,6-trimethylbenzoylphosphonate lithium salt into 2ml water, stir for 20 minutes to completely dissolve the solid, add 0mg MXene powder into the above solution, ultrasonicate for 1h, and finally add 0.12g sodium poly(p-styrene sulfonate) and stir until the solid is completely dissolved.
[0079] Diaphragm hydrogel solution: 0.47 g acrylamide monomer, 2.34 mg N,N'-methylenebisacrylamide, 2.34 mg phenyl-2,4,6-trimethylbenzoylphosphonate lithium salt, and 0.47 mg tartrazine were added to 4.2 ml water and stirred for 20 minutes to completely dissolve the solid.
[0080] N-type semiconductor hydrogel solution: Add 0.52g acrylamide monomer, 2.6mg N,N'-methylenebisacrylamide, and 2.6mg phenyl-2,4,6-trimethylbenzoylphosphonate lithium salt to 3.9ml water and stir for 20 minutes to completely dissolve the solid. Add 0.78g polydiallyldimethylammonium chloride (PDACI) solution to the above solution and continue stirring for 20 minutes. Finally, add 0mg MXene powder and ultrasonicate for 1h.
[0081] S2: Digital light-curing 3D printing:
[0082] According to the designed model, the printing layer height is set to 100μm. After the slicing is completed, 10 layers of P-type semiconductor hydrogel are first printed and cured, followed by 10 layers of membrane hydrogel, and finally 10 layers of N-type semiconductor hydrogel. The P-type semiconductor hydrogel, membrane hydrogel and N-type semiconductor hydrogel are closely fitted, and finally integrated into a high-performance integrated gel ion diode.
[0083] Embodiment 5
[0084] A method for preparing a high-performance integrated gel ion diode comprises the following steps:
[0085] S1: Configuration of digital light-curing 3D printing ink:
[0086] P-type semiconductor hydrogel solution: Add 0.57g acrylamide monomer, 2.29mg N,N'-methylenebisacrylamide, and 2.86mg phenyl-2,4,6-trimethylbenzoylphosphonate lithium salt to 2ml water, stir for 20 minutes to completely dissolve the solid, add 1mg MXene powder to the above solution, ultrasonicate for 1h, and finally add 0.29g sodium poly(p-styrene sulfonate) and stir until the solid is completely dissolved.
[0087] Diaphragm hydrogel solution: 1.05 g acrylamide monomer, 4.2 mg N,N'-methylenebisacrylamide, 5.25 mg phenyl-2,4,6-trimethylbenzoylphosphonate lithium salt, and 1.05 mg tartrazine were added to 4.2 ml water and stirred for 20 minutes to completely dissolve the solid.
[0088] N-type semiconductor hydrogel solution: Add 1.04g acrylamide monomer, 5.4mg N,N'-methylenebisacrylamide, and 6.7mg phenyl-2,4,6-trimethylbenzoylphosphonate lithium salt to 3.9ml water and stir for 20 minutes to completely dissolve the solid. Add 1.8g polydiallyldimethylammonium chloride (PDACI) solution to the above solution and continue stirring for 20 minutes. Finally, add 10mg MXene powder and ultrasonicate for 1h.
[0089] S2: Digital light-curing 3D printing:
[0090] According to the designed model, the printing layer height is set to 100μm. After the slicing is completed, 10 layers of P-type semiconductor hydrogel are first printed and cured, followed by 10 layers of membrane hydrogel, and finally 10 layers of N-type semiconductor hydrogel. The P-type semiconductor hydrogel, membrane hydrogel and N-type semiconductor hydrogel are closely fitted, and finally integrated into a high-performance integrated gel ion diode.
[0091] Embodiments 4 and 5 provide P-type semiconductor hydrogel solutions, diaphragm hydrogel solutions, and N-type semiconductor hydrogel solutions with different ratios, which can also be integrated to form high-performance integrated gel ion diodes.
[0092] In order to verify the effect of MXene on the rectification characteristics of gel ion diodes, the following schemes were tried:
[0093] Comparative Example 1
[0094] When preparing P-type and N-type semiconductor hydrogel solutions, no MXene powder is added.
[0095] The proportions of other materials used in the above scheme are the same as those in Example 2, and the printing parameters are the same.
[0096] Comparative Example 2
[0097] When preparing the P-type semiconductor hydrogel solution, MXene powder is not added, while MXene powder is added to the N-type semiconductor hydrogel solution.
[0098] The proportions of other materials used in the above scheme are the same as those in Example 2, and the printing parameters are the same.
[0099] Comparative Example 3
[0100] When preparing P-type and N-type semiconductor hydrogel solutions, no MXene powder is added.
[0101] The proportions of other materials used in the above scheme are the same as those in Example 3, and the printing parameters are the same.
[0102] Comparative Example 4
[0103] When preparing P-type and N-type semiconductor hydrogel solutions, no MXene powder is added.
[0104] The proportions of other materials used in the above scheme are the same as those in Example 3, and the printing parameters are the same.
[0105] Comparative Example 5
[0106] When preparing P-type and N-type semiconductor hydrogel solutions, no MXene powder is added.
[0107] The proportions of other materials used in the above scheme are the same as those in Example 1, and the printing parameters are the same.
[0108] Comparative Example 6
[0109] When preparing P-type and N-type semiconductor hydrogel solutions, no MXene powder is added.
[0110] The proportions of other materials used in the above scheme are the same as those in Example 1, and the printing parameters are the same.
[0111] During the experiment, in order to verify the influence of the integrated molding process on the rectification characteristics of the gel ion diode, the following schemes were tried:
[0112] Comparative Example 7
[0113] The preparation method of the non-integrated gel ion diode comprises the following steps:
[0114] S1: Digital light-curing 3D printing ink configuration:
[0115] P-type semiconductor hydrogel solution: add 0.4g acrylamide monomer, 2mg N,N'-methylenebisacrylamide, and 2.5mg phenyl-2,4,6-trimethylbenzoylphosphonate lithium salt to 2ml water, stir for 20 minutes to completely dissolve the solid, add 2mg MXene powder to the above solution, ultrasonicate for 1h, and finally add 0.15g sodium poly(p-styrene sulfonate) and stir until the solid is completely dissolved.
[0116] N-type semiconductor hydrogel solution: Add 1.12g acrylamide monomer, 5.6mg N,N'-methylenebisacrylamide, and 7mg phenyl-2,4,6-trimethylbenzoylphosphonate lithium salt to 3.9ml water and stir for 20 minutes to completely dissolve the solid. Add 2g polydiallyldimethylammonium chloride solution to the above solution and continue stirring for 20 minutes. Finally, add 5.5mg MXene powder and ultrasonicate for 1h.
[0117] S2: Digital light-curing 3D printing:
[0118] According to the design model, the printing layer height was set to 100 μm. After slicing, 10 layers of P-type semiconductor hydrogel were printed and cured. The above steps were repeated to print and cure 10 layers of N-type semiconductor hydrogel. A layer of polytetrafluoroethylene (PTFE) diaphragm was placed between the two semiconductor hydrogels, and finally assembled into a non-integrated gel ion diode.
[0119] The ion diodes with a membrane hydrogel thickness of 0.8 mm prepared in Comparative Example 1 and Comparative Example 2 were subjected to IV curve tests. The results are as follows: Figure 3 As shown in a and b, even without the addition of MXene, the gel ion diode still exhibits certain rectification characteristics, indicating that the polymer electrolyte is the reason why the ion diode has the rectification characteristics. Figure 3 d compares the IV curves of Example 2 and Comparative Examples 1 and 2. After adding MXene, thanks to the excellent conductivity of MXene, the forward current of the ion diode is significantly improved. Due to the effect of the ionic double layer, the reverse current changes little, which greatly increases the rectification ratio.
[0120] In order to verify the rectification characteristics of the integrated gel ion diode at different voltages and further determine the improvement effect of MXene on the rectification performance, the IV curve test of the gel ion diode with a membrane hydrogel thickness of 0.8mm and 0.5mm was carried out in the voltage range of ±3V. The results are as follows: Figure 4As shown in a and b, under a smaller voltage range, the integrated gel ion diode still exhibits rectification characteristics, and the addition of MXene has a more significant effect on improving the forward current. It should be noted that the reverse current also increases slightly with the addition of MXene, which may be related to the redox reaction of water in the hydrogel under reverse voltage. + and OH - The movement of the reverse current increases. Figure 4 c and d correspond to Figure 4 The rectification ratio changes of a and b. After adding MXene into the N-type hydrogel, the rectification ratio is nearly doubled. After adding MXene on both sides, the rectification ratio is also improved compared to adding MXene on one side.
[0121] While ensuring the rectification characteristics of ion diodes, we pursue high rectification ratio and high conductivity to replace the traditional diode function. Therefore, we tested and calculated the rectification ratios of 3mm, 2.8mm and 2.5mm at ±4V. Figure 5 Compared with the voltage range of ±3 V, the rectification ratio of the gel ion diode is larger at ±4 V. With the addition of MXene, the highest rectification ratio can reach 17.6, achieving a better rectification effect. Figure 5 d summarizes the rectification ratios of integrated and non-integrated (0 mm, PTFE diaphragm) gel ion diodes at ±4 V. Due to the incompatibility of the internal interface of the non-integrated gel ion diode, a large ion transmission resistance is caused. After adding MXene, the rectification ratio is improved to a certain extent, but it is still lower than that of the integrated gel ion diode without MXene. The rectification characteristics are not good, highlighting the advantages of the integrated molding process. At the same time, the integrated molding process greatly guarantees compatibility, is conducive to the rapid and effective transmission of ions, and ensures high conductivity.
[0122] like Figure 6 As shown, the integrated gel ion diode is connected in series with the LED bulb to test the rectification effect of the gel ion diode in the actual circuit. Figure 6 a is the equivalent circuit diagram when a 2.5V reverse voltage is applied. At this time, the LED bulb flashes a very weak red light in a dark environment. According to the test results of the source meter, the current in the circuit is about 0.7μA. Figure 6 b When a forward voltage of 2.5V is applied, the LED bulb emits a brighter red light. At this time, the current in the circuit is much larger than the current when the reverse voltage is applied, which is about 10μA. This shows that the gel ion diode also exhibits rectification characteristics in the actual circuit and is repeatable.
Claims
1. A high performance integrated gel ion diode, characterized in that: From top to bottom, it includes a P-type semiconductor hydrogel (1), a membrane hydrogel (2) and an N-type semiconductor hydrogel (3), and the P-type semiconductor hydrogel (1), the membrane hydrogel (2) and the N-type semiconductor hydrogel (3) are integrally formed.
2. A high performance integrated gel ion diode according to claim 1, characterized in that: The hydrogel matrix in the P-type semiconductor hydrogel (1), the diaphragm hydrogel (2) and the N-type semiconductor hydrogel (3) is polyacrylamide.
3. The method for preparing a high-performance integrated gel ion diode according to claim 1, characterized in that: By using digital light-curing 3D printing technology, a P-type semiconductor hydrogel solution, a diaphragm hydrogel solution, and an N-type semiconductor hydrogel solution are sequentially printed and cured, so that these solutions are cured into gels to form a P-type semiconductor hydrogel (1), a diaphragm hydrogel (2), and an N-type semiconductor hydrogel (3).
4. The method for preparing a high-performance integrated gel ion diode according to claim 3, characterized in that: The digital light-curing 3D printing technology comprises the following steps: S1: Configuration of digital light-curing 3D printing ink: P-type semiconductor hydrogel solution: acrylamide monomer, phenyl-2,4,6-trimethylbenzoylphosphonate lithium salt powder, and N,N'-methylenebisacrylamide powder are added to water and stirred for 20 minutes to completely dissolve the solid and make the solution clear and transparent; MXene powder is added to the above solution, ultrasonicated for 1 hour, and finally the polymer electrolyte sodium poly(p-styrene sulfonate) is added, and stirring is continued for 20 minutes to mix the two evenly, and the powder is stirred until it is completely dissolved; the mass fraction of the acrylamide monomer is 10%-20%, the mass fractions of phenyl-2,4,6-trimethylbenzoylphosphonate lithium salt and N,N'-methylenebisacrylamide are 0.05%-0.1% and 0.05%-0.08% respectively, the mass fraction of sodium poly(p-styrene sulfonate) is 5%-10%, and the concentration of MXene is 0-1mg / ml; wherein the MXene powder is an accordion-like multilayer MXene nanosheet; Diaphragm hydrogel solution: acrylamide monomer, phenyl-2,4,6-trimethylbenzoylphosphonate lithium salt powder, N,N'-methylenebisacrylamide powder and lemon yellow powder are added into water and stirred for 20 minutes to completely dissolve the solid and make the solution clear and transparent; wherein the mass fraction of acrylamide monomer is 10%-20%, the mass fractions of phenyl-2,4,6-trimethylbenzoylphosphonate lithium salt powder, N,N'-methylenebisacrylamide powder and lemon yellow are 0.05%-0.1%, 0.05%-0.08% and 0.01%-0.02% respectively; N-type semiconductor hydrogel solution: acrylamide monomer, phenyl-2,4,6-trimethylbenzoylphosphonate lithium salt powder, and N,N'-methylenebisacrylamide powder are added to water and stirred for 20 minutes to completely dissolve the solid and make the solution clear and transparent; then polydiallyldimethylammonium chloride solution is added to the above solution; stirring is continued for 20 minutes, and finally MXene powder is added and ultrasonicated for 1 hour; wherein the mass fraction of acrylamide monomer is 10%-20%, the mass fractions of phenyl-2,4,6-trimethylbenzoylphosphonate lithium salt and N,N'-methylenebisacrylamide are 0.05%-0.1% and 0.05%-0.08% respectively, the mass fraction of polydiallyldimethylammonium chloride is 3%-5%, and the concentration of MXene is 0-1mg / ml; S2: Digital light-curing 3D printing: After slicing according to the designed model, the P-type semiconductor hydrogel solution is printed and solidified first, and then the diaphragm hydrogel solution and the N-type semiconductor hydrogel solution are printed and solidified in sequence, wherein the acrylamide monomers in each solution form polyacrylamide gel solids under digital light irradiation; finally, the high-performance integrated gel ion diode is formed by integrated molding.
5. The method for preparing a high-performance integrated gel ion diode according to claim 4, characterized in that: The model is cylindrical, the radius of the model is 5-10 mm, the total thickness is 2.5-3 mm, the layer height of the 3D printing is set to 100 μm, and the curing time is 10-15 s.
6. The method for preparing a high-performance integrated gel ion diode according to claim 4, characterized in that: The size of the integrated gel ion diode is 5-10 mm in radius and 2.5-3 mm in total thickness; The thickness of the diaphragm hydrogel is 0.5-1 mm.
7. Use of the high-performance integrated gel ion diode according to claim 1 or 2 in a circuit.